Generating attosecond pulses with high ellipticity by use of He atoms. Issue 14 (16th August 2019) - Zhu, Mu-Feng; Wang, Guo-Li; Zhao, Song-Feng; Li, Xiao-Yong; Zhou, Xiao-Xin
ABSTRACT: To control the polarization of attosecond pulse trains (APTs), the most widely used way is to adjust the intensity ratio between the two components in a bicircular laser field. Here we demonstrate another effective means to obtain highly elliptically polarized APTs. For this purpose, we propose a circular-elliptical laser field, which consists of a circularly polarized field with its coplanar counter-rotating elliptical harmonic pulse, in order to generate high-order harmonics by He atom. We show that the polarization of APTs depends evidently on the ellipticity ξ of harmonic laser field. Most importantly, nearly circular APTs can be obtained with a proper ξ for ω − 3 ω driving laser field. Our results contribute to the generation of high elliptically polarized APTs with s -state atom.